Midwives' experiences of transfer in labour from a Western Australian birth centre to a tertiary maternity hospital - Kuliukas, Lesley; Lewis, L.; Hauck, Y.; Duggan, Ravani (Elsevier, 2015)
Background: When transfer in labour takes place from a woman-centred, midwifery led centre to a tertiary maternity hospital it is accepted that women are negatively affected, however the midwife's role is unevaluated, there is no published literature exploring their experience. This study aimed to describe these experiences. Methods: Giorgi's descriptive phenomenological method of analysis was used to explore the 'lived' experiences of the midwives. Seventeen interviews of transferring midwives took place and data saturation was achieved. Findings: The overall findings suggest that midwives find transfer in labour challenging, both emotionally and practically. Five main themes emerged: (1) 'The midwife's internal conversation' with subtheme: 'Feeling under pressure', (2) 'Challenged to find a role in changing circumstances' with subtheme: 'Varying degrees of support', (3) 'Feeling out of place' with subtheme: 'Caught in the middle of different models of care, (4) 'A constant support for the parents across the labour and birth process' with subthemes: 'Acknowledging the parents' loss of their desired birth' and (5) 'The midwives' need for debrief'. Conclusion: Midwives acknowledged the challenge of finding the balance between fulfilling parents' birth plan wishes with hospital protocol and maintaining safety. Transfer for fetal or maternal compromise caused anxiety and concern. The benefits of providing continuity of care were acknowledged by the midwife's knowledge of the woman and her history but these were not always recognised by the receiving team. Discussing the transfer story afterwards helped midwives review their practice. Effective communication between all stakeholders is essential throughout the transfer process.